Effect of one session of hyperbaric oxygen (2.5 ATA for 60 min) after moderate-intensity exercise on fatigue: a single-blind crossover randomized trial - Yagishita, Kazuyoshi; Aizawa, Junya; Ohji, Shunske; Hoshino, Takashi; Oyaizu, Takuya (Frontiers in Sports and Active Living, 2025)
ObjectivesAlthough insufficient delivery of oxygen may be a factor in physical and perceived fatigue, the relationship between exposure to hyperbaric oxygen (HBO) and recovery from perceived fatigue remains unexplained. The purpose of this single-blind study was to investigate the effects of exposure to HBO after long-duration, medium-intensity training on recovery from perceived fatigue.MethodsFatigue was induced in nine male university students (mean age: 21.3 years) using an ergometer exercise bike at a moderate intensity of 75% of their maximum heart rate for 60 min. Post-workout, the subjects randomly received an intervention comprising exposure to HBO or mild hyperbaric air (MHA) as a control in a single-blind experimental trial. Blood tests were conducted, and perceived fatigue was evaluated using the visual analog scale (VAS) at five time points. A crossover trial was conducted 1 week later.ResultsIn the HBO group, the pre- to post-intervention mean VAS scores for whole-body fatigue significantly improved from 48.4 to 28.7 (p < 0.001). However, in the MHA group, the improvement was not statistically significant. The majority of the hematological assessments, including C-reactive protein level, white blood cell count, creatine kinase level, lactic acid level, T-cell count, CD4/CD8 ratio, and natural killer cell count, did not show any significant between-group differences; however, the blood urea nitrogen and free fatty acids levels 1.5 h after intervention and Mg levels immediately after intervention were significantly higher in the HBO group.ConclusionsThe results of this study showed that perceived fatigue evaluated using the VAS score significantly improved in the HBO group in a blinded trial. However, this was not objectively supported by the blood test results. HBO may have effects on recovery from perceived fatigue following long-duration, moderate-intensity exercise; however, the results of this study could not determine the efficacy of HBO on exercise-induced fatigue.Clinical Trial Registrationhttps://www.isrctn.com/ISRCTN81080077, identifier ISRCTN81080077.